EFEKTIVITAS MEDIA PEMBELAJARAN MOODLE TERHADAP HASIL BELAJAR AKUNTANSI DASAR DI SMKN 1 MUARA PAWAN - Amelia Diaz Amelda; Maria Ulfah; Heni Kuswanti (Universitas Tanjungpura, 2021)
AbstractThis study focuses on knowing the effectiveness of learning outcomes in basic accountingclass X AKL at SMK N 1 Muara Pawan Ketapang by using the Moodle learning mediaapplication. The method applied in this study is a quantitative method with a Pre-Experimental Designs approach where the data collection tool used is by using tests. Thedata sources of this research were students of class X Accounting which consisted of 17women and 9 men. The data is the results of the answers to the pretest and posttest of basicaccounting class X AKL at SMKN 1 Muara Pawan Ketapang. The research data collectedwere analyzed using the normality test and n gain, then the research data was processed todetermine the learning outcomes of the basic accounting pretest and posttest scores. Thenthe results of the stratistic calculation show that the use of Moodle learning mediaapplications is effective on basic accounting learning outcomes with the magnitude of theeffectiveness that can be seen by comparing learning outcomes with the KKM and the resultsof the calculation of the effect size, which is 2.08 which is categorized as a very large effect.Keywords: Moodle, Learning Outcomes